Interplay between hybridisation gaps and unusual magnetic orders in Kondo semiconductors CeT2Al10 (T = Ru and Os). Issue 23 (2nd December 2019) - Takabatake, Toshiro; Muro, Yuji; Kawabata, Jo; Hayashi, Kyosuke; Takeuchi, Takashi; Umeo, Kazunori; Ekino, Toshikazu; Adroja, Devashibhai T.
ABSTRACT: Kondo semiconductors based on rare-earth elements possess a narrow gap in the renormalised density of states near the Fermi level. Their ground states remain nonmagnetic due to strong hybridisation of the 4 f state with conduction bands. However, in the orthorhombic compounds Ce T 2 Al10 ( T  = Ru, Os), opening of a hybridisation gap is followed by an antiferromagnetic (AFM) order at a rather high temperature T N  ≅ 28 K. Our systematic studies of the effects of electron/hole doping on the magnetic and transport properties, electron tunnelling, and spin-gap formation revealed that the hybridisation gap is indispensable for the unusual AFM order. Under uniaxial pressure, T N increases linearly as the orthorhombic b -axis parameter is decreased. Our findings support the model that a kind of charge-density wave developing along the b axis in the presence of the hybridisation gap induces the AFM order in these systems.